Potential Involvement of IL-17F in Asthma - Kyoko Ota; Mio Kawaguchi; Satoshi Matsukura; Masatsugu Kurokawa; Fumio Kokubu; Junichi Fujita; Yuko Morishima; Shau-Ku Huang; Yukio Ishii; Hiroaki Satoh; Nobuyuki Hizawa (Journal of Immunology Research)
The expression of IL-17F is seen in the airway of asthmatics and its level is correlated with disease severity. Several studies have demonstrated that IL-17F plays a pivotal role in allergic airway inflammation and induces several asthma-related molecules such as CCL20. IL-17F-induced CCL20 may attract Th17 cells into the airway resulting in the recruitment of additional Th17 cells to enhance allergic airway inflammation. We have recently identified, for the first time, that bronchial epithelial cells are its novel cell source in response to IL-33 via ST2-ERK1/2-MSK1 signaling pathway. The receptor for IL-17F is the heterodimeric complex of IL-17RA and IL-17RC, and IL-17F activates many signaling pathways. In a case-control study of 867 unrelated Japanese subjects, a His161 to Arg161 (H161R) substitution in the third exon of the IL-17F gene was associated with asthma. In atopic patients with asthma, prebronchodilator baseline FEV1/FVC values showed a significant association with the H161R variant. Moreover, this variant is a natural antagonist for the wild-type IL-17F. Moreover, IL-17F is involved in airway remodeling and steroid resistance. Hence, IL-17F may play an orchestrating role in the pathogenesis of asthma and may provide a valuable therapeutic target for development of novel strategies.